FAKTOR-FAKTOR YANG MEMENGARUHI NIAT MENGGUNAKAN KECAP LOKAL - Siahaan, S. Berto Fready; Sumarwan, Ujang; Nurrochma, Dodik Ridho (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
The purpose of this research was to analyze the determinant factors of intention of the food sellers in using the traditional soy sauces for their products. The theory of planned behavior (TPB) was used as approach to explaine the intention as the major causal for the occurrence of a certain behavior. The research was conducted in Bogor and involved the food sellers who were using the traditional soy sauces.The data collection was conducted by personal interview of 102 respondents using quesionairres. The data was processed by thedescriptive and the multiple linear regression methods.The result showed that the attitude toward behavior (Aact) and the perceived behavioral control (PBC) significantly affected the intention, while the subjective norm (SN) did not significantly affect the intention. Based on the result, the determinant factors of intention for using the traditional soy sauces were creating of profit, creating of food deliciousness, creating of welfare for local communities, accceptable price, good quality, and easiness to get.